Ascorbic acid biosensing methods: A review. (July 2022) - Malik, Meghna; Narwal, Vinay; Pundir, C.S.
Abstract: Ascorbic acid has a significant regulatory effect on neurotransmitters and enzymes in the central nervous system. In apparently healthy people, the reference range for ascorbic acid is 0.6–2 mg/dL. The variable concentration of ascorbic acid within biology fluids was found in clinical investigations to be a metric for assessing the exact amount of oxidative stress in the body's metabolism. The rise in oxidative stress is well-defined in connection with diabetes, cancer, and liver disease. There are various methods for detecting ascorbic acid which are time-consuming, necessitate sample pre-treatment and require high-cost instrumental set-up. These disadvantages were overcome by biosensing methods, as these are precise, rapid, simple, economical, and extremely sensitive. The classification, operational principles, merits and demerits of ascorbate biosensors, based on transducers, is described in this review article. Biosensors for ascorbic acid performed optimally in the pH range of 1–7.4, at room temperature, and in the ascorbic acid concentration range of 0.005–18, 000 µM, with a minimum detection limit of 0.008 µM, at a working potential of −0.05–3.8 V. Ascorbic acid levels in blood, serum, and urine were monitored using these biosensors. Ascorbate biosensors' economic advancement and commercialisation are suggested. Highlights: The variable concentration of ascorbic acid is well-defined in connection with diabetes, cancer, and liver diseases. In apparently healthy people, the reference range for ascorbic acid is 0.6–2 mg/dL. Present review summarises the classification and principles of various biosensing methods for determination of ascorbic acid. Ascorbic acid biosensors' economic future for advancement and commercialisation are examined in the review.